WELCOME SPEECH BY THE PRIME MINISTER OF THE REPUBLIC OF LITHUANIA AT THE INTERNATIONAL SCIENTIFIC CONFERENCE ON “BOOK CULTURE OF THE LIFE-TIME OF KRISTIJONAS DONELAITIS IN THE MULTICULTURAL SOCIETY OF PRUSSIA” - BUTKEVIČIUS, ALGIRDAS (Knygotyra, 2015)
...